Pengembangan Bahan Ajar English Phonology dan Strategi Pembelajarannya - Erika Agustiana; M Sulhan; Saidatun Nafisah (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The aim of the study was to develop English teaching material and the strategy. This study used library method. The data were obtained from phonology book, archives and other literature resources. The finding showed two developed points. Teaching material was arranged to cover the whole material which was taught and made according to KKNI. The discussion dealt with English pronunciation problems by native Indonesian was included in the material as the result of problem solving. The teaching strategy in this course was blended learning method. The method concerned on the process of learning activities and assignment. The method was selected in order that the students were able to use the technology and sharpen their digital literacy. In conclusion, the teaching material was developed based on KKNI and the strategy used was blendes learning. Keywords: Teaching Material, Strategy, English Phonology